2009
DOI: 10.1073/pnas.906637106
|View full text |Cite
|
Sign up to set email alerts
|

Sleep–wake regulation and hypocretin–melatonin interaction in zebrafish

Abstract: In mammals, hypocretin/orexin (HCRT) neuropeptides are important sleep-wake regulators and HCRT deficiency causes narcolepsy. In addition to fragmented wakefulness, narcoleptic mammals also display sleep fragmentation, a less understood phenotype recapitulated in the zebrafish HCRT receptor mutant (hcrtr؊/؊). We therefore used zebrafish to study the potential mediators of HCRT-mediated sleep consolidation. Similar to mammals, zebrafish HCRT neurons express vesicular glutamate transporters indicating conservati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
165
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 170 publications
(175 citation statements)
references
References 36 publications
8
165
2
Order By: Relevance
“…Fish show brief periods during which they stop swimming and are immobile, with increased arousal threshold; these behaviors occur nearly exclusively during the night (zebrafish are diurnal) (Zhdanova et al 2001;Yokogawa et al 2007;Appelbaum et al 2009). Recent work leveraging the genetic tractability of this vertebrate model organism has uncovered a role for melatonin in conveying the circadian control of sleep timing (Zhdanova et al 2001;Gandhi et al 2015).…”
Section: Fish Sleepmentioning
confidence: 99%
See 2 more Smart Citations
“…Fish show brief periods during which they stop swimming and are immobile, with increased arousal threshold; these behaviors occur nearly exclusively during the night (zebrafish are diurnal) (Zhdanova et al 2001;Yokogawa et al 2007;Appelbaum et al 2009). Recent work leveraging the genetic tractability of this vertebrate model organism has uncovered a role for melatonin in conveying the circadian control of sleep timing (Zhdanova et al 2001;Gandhi et al 2015).…”
Section: Fish Sleepmentioning
confidence: 99%
“…Moreover, zebrafish utilize the hypocretin/orexin signaling system (Zhdanova 2006;Appelbaum et al 2010;Panula et al 2010;Yelin-Bekerman et al 2015), abnormalities in which are known to cause the human sleep disorder narcolepsy. Similar to its mammalian analog, the zebrafish hypocretin system is located in the hypothalamus and regulates sleep-wake transitions (Prober et al 2006;Yokogawa et al 2007;Appelbaum et al 2009;Elbaz et al 2013). It comprises merely 20-60 hypocretin neurons, several orders of magnitude fewer than those found in mice (Kaslin et al 2004).…”
Section: Fish Sleepmentioning
confidence: 99%
See 1 more Smart Citation
“…In zebrafish, the neuronal circuit organization and the circadian and homeostatic (compensatory increased sleep following sleep deprivation) processes that regulate sleep are largely conserved with mammals (Zhdanova et al, 2001;Prober et al, 2006;Yokogawa et al, 2007;Rihel et al, 2010). The zebrafish HCRT neuronal network is simple and comprises only ϳ20 -60 hypothalamic neurons that project to several areas in the brain, including putative wake-and sleep-regulating neurons, such as the hindbrain and pineal gland, respectively (Kaslin et al, 2004;Faraco et al, 2006;Prober et al, 2006;Appelbaum et al, 2009Appelbaum et al, , 2010. Global overexpression of HCRT in larval zebrafish induces wakefulness (Prober et al, 2006) and the HCRT-receptor mutant (hcrtr Ϫ/Ϫ ) adult zebrafish exhibits sleep fragmentation during the night (Yokogawa et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In this context, a recent study suggested a major role of iGluRs and ORX interactions since it has been shown that glutamate agonists initiate excitatory postsynaptic currents by increasing the number of c-Fos-positive hypothalamic ORX neurons (Eyigor et al 2012) as well as ORX-A-dependent anxiety-like behaviors in the bed nucleus of the stria terminalis (Lungwitz et al 2012). Although a growing amount of data regarding ORX and iGluRs cross-talking events has been reported in mammals, to date little is known on aquatic vertebrates, aside from the fact that glutamatergic phenotype of ORX neurons is well conserved across vertebrates, especially in fish (Appelbaum et al 2009). …”
Section: Introductionmentioning
confidence: 99%